(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Purpose: To assess the status of the immune system in patients with ocular demodicosis. Methods: This study was conducted at the Immunology Laboratory and Clinical Diagnostics Laboratory of SI “The Filatov Institute of Eye Diseases and Tissue Therapy of the National Academy of Medical Sciences of Ukraine”. We examined 47 patients with chronic ocular demodicosis (mean age, 29.7 ± 17.4 years) who were treated at the Consultative Polyclinic of SI “The Filatov Institute of Eye Diseases and Tissue Therapy of the NAMS of Ukraine”. The control group included 20 healthy donors (mean age, 32.8 ± 15.2 years). Monoclonal antibodies (McABs) and fluorescence microscopy were used in immunohistochemistry studies. Spreadsheets and IBM SPSS Statistics (Demo) software were employed for statistical analysis. Results: Patients with ocular demodicosis exhibited changes in immune system function, reductions in neutrophil phagocytic activity and the absolute count and percentage of CD3 and increases in the neutrophil-to-lymphocyte ratio and percentage of CD16. Treatment for ocular demodicosis should include not only anti-parasitic therapy, but also anti-inflammatory therapy and immune correction.